Sediment trap-derived particulate matter fluxes in the oligotrophic subtropical gyre of the South Indian Ocean. (January 2021) - Harms, Natalie C.; Lahajnar, Niko; Gaye, Birgit; Rixen, Tim; Schwarz-Schampera, Ulrich; Emeis, Kay-Christian
Abstract: Oligotrophic areas cover about 75% of the ocean's surface, and these ocean regions are predicted to expand under global warming scenarios. To evaluate impacts on global marine biogeochemical cycles and changes in ocean-atmosphere carbon fluxes, it is essential to understand particulate matter fluxes and determine the amount of organic carbon that is exported to the ocean's interior. The oligotrophic Indian Ocean subtropical gyre (IOSG) is one of the least explored ocean regions in terms of particulate matter fluxes. Sediment trap-based particulate matter fluxes determined during a 4-year time series provide new information on the nature of export fluxes, their controlling factors, and on the spatial and temporal variability of oceanic processes in the IOSG. Trap-averaged total mass fluxes ( 9.8 ± 3.7 mg m −2 day −1 ), as well as particulate organic carbon (POC) fluxes (0.50 ± 0.15 mg m −2 day −1 ) measured at 500–600 m above bottom (2600–3500 m water depth) are among the lowest fluxes recorded worldwide. These low flux values are a result of strongly stratified and nutrient-depleted upper waters in the gyre. Such oligotrophic conditions lead to low primary production rates in a relatively homogeneous and isolated ocean region. Consequently, we observe an almost constant rain of POC fluxes in space and time, although minor variations in the net primary production (NPP) and in the sea surface temperature (SST) are seen in satellite surveys and model estimations. Factors contributing to the lack of seasonality in the POC fluxes are intense organic matter degradation, variations in the ocean mixed layer depth (OMLD), and impacts of physical mixing (surface wind stress, cyclonic eddies). Preliminary estimates indicate that the average POC export efficiency (ε = 0.03 ± 0.01) is extremely low in the IOSG. Assuming that the IOSG, as well as comparable ocean regions, will expand under climate warming conditions, it is of major importance to investigate POC export fluxes to the deep ocean in order to predict changes in the global carbon cycle during the next decades. Highlights: First sediment trap-based particulate matter fluxes in the subtropical Indian Ocean. The oligotrophic Indian Ocean has the world's lowest recorded organic carbon fluxes. No correlation between net primary production and particulate organic carbon export. Less seasonal and spatial variability in organic carbon fluxes in the Indian Ocean gyre.